WADAH TUNGGAL ORGANISASI ADVOKAT DAN PENGARUHNYA TERHADAP PROFESI ADVOKAT DI INDONESIA: Ilham Fajri - admin, admin (Reformasi Hukum, 2017)
The impact of the PERADI split affected the appointment of a new advocate in which each of the camps felt entitled to inaugurate an advocate. Then on the split was issued Letter of Chief Justice of the Supreme Court Number 73 / KMA / HK.01 / IX / 2015 on Shedding Advocate. Letter of Chief Justice of the Supreme Court Number 73 / KMA / HK.01 / IX / 2015 concerning Advocate Slaughter issued on September 25, 2015 in its essence states that any advocate organization which can initiate the taking of oath or promise must meet the requirements as stipulated in Law Number 18 Year 2003 on Advocates. Therefore, PERADI is no longer a single container as mandated by Law No. 18/2003 on Advocates This study aims to discover the dynamics of the establishment of a single forum of advocate organizations and their influence on the advocate profession and its legal impact. The approach used in this study using normative juridical approach is the method of legal research conducted by examining the library materials or secondary materials.